2012
DOI: 10.1007/s10706-012-9497-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Response of the Foundations Resting on a Two-layered Soil Underlain by a Rigid Layer

Abstract: The present experimental investigations study the effect of layering over rigid base on the dynamic behavior of foundation under vertical mode of vibration. Model block vibration tests were conducted on a rigid surface footing resting on different layered soil systems underlain by rigid base. The rigid base was used to simulate the presence of bedrock.The tests were carried out in a pit of size 2.0 m 9 2.0 m 9 1.9 m (deep) using a concrete footing of size 0.4 m 9 0.4 m 9 0.1 m. A rotating mass type mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The responses obtained from the block vibration tests were further utilized to evaluate the dynamic properties of soil (γ res , G, and C u ). The magnitude of G varies perceptibly with the intensity of the applied force and the number of loading cycles [5], whereas C u and γ res vary continuously across the soil bed [25]. The magnitudes of γ res , G, and C u were determined using Eqs.…”
Section: Dynamic Properties Of Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…The responses obtained from the block vibration tests were further utilized to evaluate the dynamic properties of soil (γ res , G, and C u ). The magnitude of G varies perceptibly with the intensity of the applied force and the number of loading cycles [5], whereas C u and γ res vary continuously across the soil bed [25]. The magnitudes of γ res , G, and C u were determined using Eqs.…”
Section: Dynamic Properties Of Soilmentioning
confidence: 99%
“…The shape of the foundation influences the dynamic properties of soil, such as approximate maximum dynamic shear strain developed in soil (γ res ), shear modulus (G), and elastic uniform compression coefficient (C u ). The dynamic properties of soil vary significantly over a range of loading intensities in block vibration tests [5]. Hence, it is a gripping task to investigate the influence of footing shape on the system characteristics of machine foundations.…”
Section: Introductionmentioning
confidence: 99%
“…Coulier et al (2015) investigated the efficacy of jet grout columns in mitigating the rail induced vibration through the field and numerical investigation. Various studies reported the benefits of changing the soil profile of the foundation bed in reducing the amplitude of machine vibration (Baidya and Rathi, 2004;Baidya et al, 2006;Mandal et al, 2012). In addition, the significant improvement in natural frequency of the foundation bed was observed in the presence of stiff layer nearer to the surface footing.…”
Section: Type Of Vehicle Train Truck Bus Carmentioning
confidence: 99%
“…The soil reaction modeling allows one to determine the dominant frequencies of a local ground site, to estimate the enhancement of seismic oscillations by local soils [With, Bodare, 2007;Hosseini, Pajouh, 2010;Kumar et al, 2020], and to obtain accelerograms and response spectra of soil oscillations on the surface. Information on the probabilistic characteristics of seismic oscillations on the soil surface is required for evaluating the critical dynamic stresses and strains that cause loss of soil DOI: https://doi.org/10.24028/gzh.v43i2.230186 stability and, consequently, the destruction of buildings and structures [Gutowski, Dym, 1976;Takemiya, Yamada, 1981;Mandal et al, 2012] located on such ground.…”
mentioning
confidence: 99%